Understanding The Digital Readiness Level of Young Milennials in Bandung City (Journal of Business and Management, 2021)
The digital era created a new gap in the middle of the economic process in the company. This gap makes the company is still confusing to manage the talent whether managing and developing the talent based on their skills or re-skilling to the digital skills. The main actor on this era is young millennials people who in 10-24 years old and ready to join in the workforce. By using a quantitative approach with questionnaire method and descriptive analysis, the researcher would be measuring the readiness level of young millennials. The researcher was limited the scope and do this research in Bandung City. The researcher also used a framework from DQ Institute as a main framework on this research which is Digital-Intelligence-Quotient. Using this research method and framework, the researcher has already defined that most of respondents have ready to face the digital era and mastered in the future workforce competency, it could be seen from the result isthe young millennials have high scores in every level which is around 70% - 86%. Meanwhile, there are still young millennials that has a low score. Therefore, the young millennials should create a right strategy to increase their future workforce competency and become an individual that wise, competent, and future-ready digital citizens who successfully use, control, and create technology to enhance humanity.Keyword: Digital Readiness, Future Workforce Competency, and Young Millennials